Study of the Prevalence of Human Papillomavirus Genotypes in Jeddah, Saudi Arabia - Mai M. El-Daly; Arwa A. Faizo; Shahad A. Madkhali; Nashwa F. Aldardeir; Nassrin A. Badroon; Norah A. Uthman; Rahaf T. Alqawas; Ahmed A. Mousa; Safaa A. Turkistani; Esam I. Azhar (Journal of Epidemiology and Global Health)
Abstract Human papillomavirus (HPV), a common sexually transmitted infection, includes over 200 types, some linked to genital warts and various cancers, including cervical, anal, penile, and oropharyngeal cancers. In Saudi Arabia, an estimated 10.7 million women aged 15 years and older are at risk of HPV-related cervical cancer. This study assessed HPV prevalence, genotype distribution, awareness, and health behaviors among females in Jeddah, Saudi Arabia. Pap smear samples were collected from 106 women attending gynecology clinics at King Abdulaziz University Hospital and were analyzed using nested PCR and Sanger sequencing. Results showed a 15.1% HPV positivity rate, with genotypes of HPV 16, 6, and 58 identified. HPV 16 was the most prevalent (43.75%), particularly among women aged 35–44. In addition, over 60% of the participants were unaware of the link between HPV and cervical cancer, or the availability of vaccines, indicating significant knowledge gaps in the population. These findings underscore the urgent need for comprehensive HPV surveillance and targeted public health interventions in Saudi Arabia. This study emphasizes the importance of HPV vaccination programs, increased screening, and educational campaigns to address the high prevalence of high-risk genotypes, particularly HPV 16. Tailored strategies are crucial to reducing HPV-related health risks, especially for high-risk age groups and under-informed populations. The data provide a foundation for improving HPV prevention and reducing the burden of related diseases in the Saudi population.